Penerapan Assignment Model Pada Pintu Masuk Kedatangan Wisatawan Asing Sebagai Strategi Pengembangan Pariwisata Di Indonesia - Rambu Yetti Kalaway (Universitas Kristen Wira Wacana Sumba, 2014)
Assignment model is one of the solution of the Linear Programming to solve problems in various fields, including in the field of tourims economics. The high level of tourism in the Indonesia make the government decision making is very crucial, so this research aim to see potential tourists entering Indonesia through various entrances in Indonesia. The results show that the five entrances, namely Soekarno-Hatta Airport, Ngurah Rai Airport, Polonia Airport, Batam and Juanda Airport specialize on five nationalities namely China, Australia, Malaysia, Singapore, and Taiwan. Thus it can be concluded that the role of the Government of the Republic of Indonesia (the authority of Kemenparekraf) in determining a strategic entrance to receive foreign tourists who enter is crucial, because the points will have an impact on strategic decisions, such as the development of facilities and infrastructure of local transportation, hotels, restaurants, labor, and other technical stuff. Keywords: tourism economics, assignment model, tourists entrance